CAPRIN1/TYMS/MTHFD2 axis promotes EMT process in nasopharyngeal carcinoma development - Wang, Kunrong; Yu, Hanbing; Guo, Shuang; Sun, Guihu; Cao, Hongwei; Xing, Dongsheng; Li, Dawei; Yan, Aihui (The international journal of biochemistry & cell biology, 2025)
Nasopharyngeal carcinoma (NPC) is a type of malignant tumor occurring in the nasopharynx. It frequently leads to treatment failure after metastasis, often resulting from epithelial-mesenchymal transition (EMT). Thymidylate synthetase (TYMS) is a key enzyme involved in DNA synthesis and replication. Currently, the role of TYMS and its mechanism of upstream and downstream in EMT of NPC is unclear. NPC cell lines HK-1 and C666–1 were used in this study. Lentivirus carrying TYMS knockdown and overexpressed plasmids were used to regulate TYMS expression. Cell migration and invasion were examined using the wound-healing and Transwell assays, respectively. C666–1 cells were injected into the axilla and tail vein of mice to form subcutaneous tumors and construct lung metastasis model, respectively. RNA immunoprecipitation assay was used to examine the interaction between protein and mRNA. RNA-seq was performed to explore the downstream regulatory mechanism of TYMS. TYMS was highly expressed in NPC tissues. TYMS silencing and upregulation inhibited and promoted EMT processes in NPC cells, respectively, as demonstrated by the expression of EMT-related proteins, including E-cadherin, Slug, MMP2, and MMP9. Cytoplasmic activation/proliferation-associated protein-1 (CAPRIN1), a protein bound with TYMS mRNA, promoted the EMT process in NPC cells. Meanwhile, TYMS knockdown reversed the effect of CAPRIN1 overexpression. Methylenetetrahydrofolate dehydrogenase 2 (MTHFD2) was down-regulated following TYMS silencing. MTHFD2 knockdown abolished the effect of TYMS overexpression. CAPRIN1/TYMS/MTHFD2 axis drives the EMT process and thus promotes NPC development, which is a promising target in therapy and adjuvant therapy of NPC.